Prognostic value of serum Troponin T in unstable angina - Katus, Hugo; Giannitsis, Evangelos (Clinical chemistry, 2018)
Featured Article: Hamm CW, Ravkilde J, Gerhardt W, Jørgensen P, Peheim E, Ljungdahl L, et al. The prognostic value of serum troponin T in unstable angina. N Engl J Med 1992;327:146-50.2 Our work on biomarkers of myocardial injury started in 1978 when the diagnosis of myocardial infarction (MI)3 was based on the WHO criteria. At that time, total creatine kinase and lactate dehydrogenase enzyme activity assays were commonly used, and creatine kinase isoenzyme (M, muscle; B, brain; CK-MB) measured as either enzyme activity or protein mass was considered the most clinically sensitive and specific biomarker for MI diagnosis. However, clinical studies indicated that patients with chest pain who were sent home from the emergency room with a diagnosis of “myocardial infarction excluded” had a survival rate similar, or even worse, to patients admitted with acute MI (1). Motivated by the imperfect clinical specificity and sensitivity of cardiac enzyme assays for diagnosis of MI and the advances …